PENGARUH PERENCANAAN PAJAK, PENGHINDARAN PAJAK, RISIKO PAJAK, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Muhammad Ardia Al Farisi; Darsono Darsono (Diponegoro Journal of Accounting, 2025)
This study is to obtain results from tests conducted on the effects of tax planning, tax avoidance, tax risk, and financial performance on company value, as previous studies have shown varying results, necessitating further testing. This study uses a quantitative approach with multiple linear regression analysis. The data used is secondary data obtained from the annual financial reports of companies in certain sectors during the period 2021 to 2023. Data testing was carried out through classical assumption testing, regression analysis, and simultaneous and partial testing to measure the strength and direction of the influence between variables. The results of this study prove that the classical assumption test on each variable is normally distributed, does not experience multicollinearity, does not contain autocorrelation, and does not exhibit heteroscedasticity. The F-statistic test showed that the independent variables collectively do not influence the dependent variable. This study found that tax planning and profitability significantly influence firm value, while tax avoidance, tax risk, and liquidity do not significantly influence firm value.